2009
DOI: 10.1007/s00011-009-0054-2
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models of asthma: a comparison between C57BL/6 and BALB/c strains regarding bronchial responsiveness, inflammation, and cytokine production

Abstract: Objective Animal models of asthma mimic major features of human disease. Since the genetic background of experimental animals might affect hyperresponsiveness and inflammation, we studied its potential influence and the mechanisms leading to differences in strains. MethodsWe applied a mouse model of allergic asthma to BALB/c and C57BL/6 mice.Results BALB/c mice displayed greater levels of airway reactivity to methacholine than C57BL/6 mice. Moreover, BALB/c mice exhibited higher numbers of mast cells in lung t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
132
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(149 citation statements)
references
References 32 publications
9
132
1
7
Order By: Relevance
“…In this context, OVA-challenged Mmp9-deficient mice displayed lower eosinophilia and hyperresponsiveness (9), whereas other authors using a different experimental protocol (far higher doses of allergen) reported increased eosinophilia in Mmp9 KO mice (13). The importance of the experimental protocol used to assess a phenotype in mice is further highlighted by various reports stating that there are important differences when considering various strains of mice (32,33). Notably, the present study provides evidence for similar exacerbated eosinophilia and increased AHR in Adamts12 2/2 mice of similar background, sensitized and challenged with two different allergens, the "classical" OVA and the very significant and widespread allergen for human asthmatics, HDM.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, OVA-challenged Mmp9-deficient mice displayed lower eosinophilia and hyperresponsiveness (9), whereas other authors using a different experimental protocol (far higher doses of allergen) reported increased eosinophilia in Mmp9 KO mice (13). The importance of the experimental protocol used to assess a phenotype in mice is further highlighted by various reports stating that there are important differences when considering various strains of mice (32,33). Notably, the present study provides evidence for similar exacerbated eosinophilia and increased AHR in Adamts12 2/2 mice of similar background, sensitized and challenged with two different allergens, the "classical" OVA and the very significant and widespread allergen for human asthmatics, HDM.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we performed our experiments using OVA in C57BL/6 mice who have been shown to be less responsive to metacholine compared with other mouse strains such as BALB/c (38,39). It was further suggested that the genetic background of mice influences several aspects of the acute allergic phenotype, including airway hyperresponsiveness (38,39).…”
Section: Discussionmentioning
confidence: 97%
“…C57BL/6 mice tend to have a reduced AHR response in comparison to BALB/c mice (15,16), and this was the case in response to Pneumocystis as well. The C57BL/6 mice we tested required a higher dose of methacholine than did BALB/c mice (30 versus 20 mg/ml aerosolization) to reach significantly elevated Penh values.…”
Section: Time Course Of Ahr In Balb/c Versus C57bl/6 Micementioning
confidence: 91%